Sclerotherapy in the Management of Oral Mucocele: A Literature Review - Trupti Vijay Gaikwad; Anuj Paul Maini; Arunima Sarma; Sukanya Das; Sayali Lokhande; Shristi Rakesh Prasad (Journal of International Clinical Dental Research Organization, 2022)
Mucocele is a mucous-filled cavity that can occur at various locations in the body including the oral cavity. There are various treatment options for mucoceles ranging from surgery, laser surgery, cryosurgery, etc. Due to the invasive surgical procedures and high chances of recurrence even after surgery, the focus of interest has now shifted to nonsurgical ways of management which show negligible side effects including the use of corticosteroids and sclerotherapy using various drugs. Further, no need for local anesthesia is an added advantage of the sclerotherapy procedure.